2017
DOI: 10.1111/jam.13383
|View full text |Cite
|
Sign up to set email alerts
|

Candida pyralidaekiller toxin disrupts the cell wall ofBrettanomyces bruxellensisin red grape juice

Abstract: Candida pyralidae shows potential to be used as a biocontrol agent against B. bruxellensis in grape juice/wine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
(134 reference statements)
0
10
0
2
Order By: Relevance
“…Nevertheless, its effectiveness was studied in a laboratory medium. In white and red wine, the toxins showed that only seven strains, out of 15 B. bruxellensis strains studied, present sensitivity in the wine matrix [27]. Later, the same authors demonstrated that toxins CpKT1 and CpKT2 can cause damage to cell walls in B. bruxellensis sensitive strains [28].…”
Section: Control Of B Bruxellensismentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, its effectiveness was studied in a laboratory medium. In white and red wine, the toxins showed that only seven strains, out of 15 B. bruxellensis strains studied, present sensitivity in the wine matrix [27]. Later, the same authors demonstrated that toxins CpKT1 and CpKT2 can cause damage to cell walls in B. bruxellensis sensitive strains [28].…”
Section: Control Of B Bruxellensismentioning
confidence: 97%
“…Several investigation groups have focused on the search of antimicrobial peptides (AMPs), which have been studied as different microorganism agent controllers at clinical or industrial importance [27].…”
Section: Control Of B Bruxellensismentioning
confidence: 99%
“…Ponadto toksyny te nie wpływały negatywnie na rozwój drożdży S. cerevisiae oraz bakterii kwasu mlekowego [57]. Antagonistyczne działanie tych toksyn wobec D. bru xellensis polega na uszkodzeniu ściany komórkowej wrażliwych drożdży [56].…”
Section: Wykorzystanie W Winiarstwieunclassified
“…Apart from the use of P. membranifaciens CYC 1086 and PMKT2, killer toxins from Ustilago maydis [10], Torulaspora delbrueckii (TdKT) [9], Kluyveromyces wickerhamii (Kwkt), Wickerhamomyces anomalus (Pikt) [183] and Candida pyralidae (CpKT1) [184] and the production of pulcherriminic acid by Metschnikowia pulcherrima (without a real killer activity but depleting biologically available iron from the medium) [190] have been reported as useful to control Brettanomyces spoilage. Continuing in the enology context, results from Alonso et al (2015) and Labbani et al (2015) conclude that a synergistic effect was operating using PMKT [185] and Pkkp (from P. kluyveri ) [8] killer toxins, respectively, in combination with potassium metabisulfite, against wine spoilage yeasts such as Zygosaccharomyces or Dekkera/Brettanomyces species. Recently, Velazquez and coworkers described the utility of mixed-inoculation with killer and sensitive yeast strains to speed cell death during second fermentation of sparkling-wines to release of certain compounds from autolyzed yeast cells [181].…”
Section: Applications Conclusion and Future Perspectives Of P Mmentioning
confidence: 99%